Properties of polyurethane foams with oxamide and borate groups - Zarzyka, Iwona (Publishing House of Lviv Polytechnic National University, 2013)
The conditions of polyurethane foams preparation with the use of new boroorganic compounds as polyols have been presented. The new polyols have been obtained by two methods: in reactions of N,N’-bis(2- hydroxyethyl)oxamide (BHEOD) and boric acid (BA) with excess of ethylene carbonate (EC) and in reactions of BHEOD esterified with BA with excess of EC. The results of determination of foaming process parameters as well as of investigation of the foams properties have been given. Визначено умови приготування пінополіуретанів з використанням нових бороорганічних сполук, таких як поліоли. Показано, що нові поліоли отримані двома способами: реакцією N,N'-біс (2-гідроксіетил)оксаміду (BГЕОД) і борної кислоти (БК) з надлишком етиленкарбонату (ЕК) і реакцією етерифікації ВГЕОД з БК з надлишком ЕК. Приведено результати визначення параметрів процесу спінювання і дослідження властивостей піни.
Властивості пінополіуретанів з оксамідними і боратними групами
Keywords: rigid polyurethane foams; oxamide; boric acid; hydroxyalkylation; modification of structure; thermal stability; compressive strength; жорсткі пінополіуретани; оксамід; борна кислота; гідроксіалкілювання; модифікація структури; термостійкість; міцність на стиснення